Self-Reported Spatial Hearing Abilities Across Different Cochlear Implant Profiles - Perreau, Ann E. (Am J Audiol, 2014)
PURPOSE: The goal of this study was to determine how self-reported spatial hearing abilities differ across various cochlear implant (CI) profiles and to examine the degree of subjective benefit following cochlear implantation across different groups of CI users. METHOD: This was a retrospective study of subjective spatial hearing ability of CI recipients. The subjects consisted of 99 unilateral CI users, 49 bilateral CI users, 32 subjects with a CI and contralateral hearing aid (bimodal users), and 37 short-electrode CI users. All subjects completed the Spatial Hearing Questionnaire (Tyler, Perreau, & Ji, 2009), a questionnaire assessing spatial hearing ability, after implantation, and a subset of the subjects completed the questionnaire pre- and postimplantation. RESULTS: Subjective spatial hearing ability was rated higher for the bilateral and short electrode CI users compared to the unilateral and bimodal users. There was no significant difference in subjective spatial hearing performance between the bilateral and short electrode CI users and the unilateral CI and bimodal users. A separate analysis of pre- and postimplant performance revealed that all CI groups reported significant improvements in spatial hearing ability after implantation. CONCLUSION: This study suggests that there are substantial differences in perceived spatial hearing ability among unilateral and bimodal CI users compared with bilateral and short electrode CI users.